Layanan Kesehatan Modern di Jawa sebagai Penyokong Kolonialisme, Penyebaran Agama dan Budaya, Abad XVII-XX - Dadan Adi Kurniawan; Ilham Putra Pratama (Universitas Hamzanwadi, 2025)
This study examines the development of modern health service centers in Java as a supporter of economic colonialism, evangelism, and the spread of culture in the 17th century to the first half of the 20th century. This study uses a historical method consisting of five steps, namely topic selection, heuristics, criticism, interpretation, and historiography. The primary source used is the Memori Serah Jabatan which is supported by credible and relevant secondary sources such as journals, books and scientific articles. This study uses a political economy and political culture approach as an analytical tool. The main focus of this study includes: the development of pre-colonial health services, early traces of health services for trade-military interests, health services as a supporter of economic colonialism, health services as a medium for the spread of religion and culture and patterns of development and organization of modern health services. The results of the study show that health services in Java underwent a significant transformation from the pre-colonial era to the colonial period, where health services not only functioned as a means of physical healing, but also became a strategic instrument in supporting various colonial agendas, especially in the economic, socio-religious, and socio-cultural aspects. Health services in Java during this period not only functioned as a supporter of economic colonialism but also as a medium for the spread of religion and culture that confirmed colonial influence.